Bibliometric and visual analysis of chemotherapy-induced nausea and vomiting (2004-2023) - Tian, Shao-Chuang; Yang, Jing; Li, Xin; Huang, Rong-Xia; Chen, Jian (Frontiers in Oncology, 2024)
Background: Patients undergoing chemotherapy often encounter troubling and common side effects, notably Chemotherapy-induced nausea and vomiting (CINV). This side effect not only impairs the patient's quality of life but could also result in the interruption or discontinuation of the chemotherapy treatment.Consequently, research into CINV has consistently remained a focal point in the realm of clinical medicine. In this research domain, bibliometric analysis has not been conducted. The purpose of this study is to deliver a thorough summary of the knowledge framework and key areas of interest in the field of Chemotherapy-induced nausea and vomiting, using bibliometric methods. This approach aims to furnish novel concepts and pathways for investigators working 2 in this area.Methods: Publications focusing on Chemotherapy-induced nausea and vomiting, spanning from 2004 to 2023, were identified using the Web of Science Core Collection (WoSCC) database. Tools such as VOSviewer, CiteSpace, and the R package "bibliometrix" were employed for this bibliometric analysis.Results: This research covers 734 publications from 61 countries, with the United States and China being the primary contributors. There has been a significant rise in the volume of papers published in the most recent decade compared to the one before it, spanning over the past twenty years. However, the annual publication rate in the last ten years has not shown a significant upward trend.